Graffiti on earthenware from Sigarra (Els Prats del Rei, Barcelona) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper offers the first comprehensive edition, following autopsy, of the graffiti on earthenware found at the Ibero-Roman site of Sigarra (now Els Prats de Rei in the province of Barcelona).
Keywords: Epigraphy; Earthenware; Iberian language; Sigarra; Lacetani